Tailoring deep level surface defects in ZnO nanorods for high sensitivity ammonia gas sensing - Suranan Anantachaisilp (2018)
© 2014 American Chemical Society. The influence of deep level surface defects on electrical and gas sensing properties of ZnO nanorods NH3(g) sensors was studied. ZnO nanorods 50-60 nm in diameter were synthesized via low-temperature hydrothermal growth at 90°C on sapphire substrates. The as-grown nanorods exhibited a cathodoluminescence (CL) peak centered at 1.90 eV (YL), attributed to LiZndeep acceptors or O interstitials. Subsequent annealing in O2at 1 atm and Zn vapor at 650°C produced broad CL peaks centered at 1.70 eV (RL) and 2.44 eV (GL), respectively. The RL and GL have been ascribed to acceptor-like VZnand donor-like VOrelated centers, respectively. Electrical and gas sensing measurements established that the NH3gas response sensitivity was 22.6 for O2anneal (RL), 1.4 for Zn vapor anneal (GL), and 4.1 for the as-grown (YL) samples. Additionally, treatment in H-plasma quenched the RL and inverted the NH3electrical response due to the incorporation of H donors. Changes in the gas sensing response are explained by a shift in the position of the ZnO Fermi level relative to the chemical potential of NH3gas due to the creation of near surface donor or acceptors. These data confirm that ZnO nanorods arrays can be tailored to detect specific gas species. (Chemical Equation Presented).